2006
DOI: 10.1051/0004-6361:20054683
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation of Fe XVI: radiative and excitation rates

Abstract: Aims. In this paper we report calculations for energy levels, radiative rates, collision strengths, and effective collision strengths for transitions in Fe XVI. Methods. For energy levels and radiative rates we have used the General purpose Relativistic Atomic Structure Package (grasp), and for the compuations of collision strengths the Dirac Atomic R-matrix Code (darc) has been adopted. Results. Energies for the lowest 39 levels among the n ≤ 7 ( ≤ 4) configurations of Fe XVI are reported. Additionally, radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…However, the data of Younis et al (2007) show a large scatter. Sampson et al (1990), KON98 to Kimura et al (1998), and AK06 to Aggarwal & Keenan (2006), for Fe 15+ . NIST compiled data are given for lower charge ions.…”
Section: Structure: Gf-valuesmentioning
confidence: 97%
See 3 more Smart Citations
“…However, the data of Younis et al (2007) show a large scatter. Sampson et al (1990), KON98 to Kimura et al (1998), and AK06 to Aggarwal & Keenan (2006), for Fe 15+ . NIST compiled data are given for lower charge ions.…”
Section: Structure: Gf-valuesmentioning
confidence: 97%
“…2a. The data of Aggarwal & Keenan (2006) Kimura et al (1998) reported the g f -values between LS terms. We partition statistically -such an assumption is a good one at low nuclear charge.…”
Section: Structure: Gf-valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sampson et al (1990) performed relativistic DW calculations for this ion, and the data are available within CHIANTI. Cornille et al (1997) Aggarwal & Keenan (2006) perfomed a calculation with the Dirac Atomic R-matrix Code (DARC). These data were used by Keenan et al (2007) to show that reasonable agreement for the A85 data was present, although they did not discuss the temperature sensitivity of these lines.…”
Section: Fe XVImentioning
confidence: 99%